A Survey on Administrative System Performance of Medical Sciences Universities of Tehran Based on Stevenson\'s Entrepreneurial Management Model - K Talebi; R Dehghan; A Arabioun (Tehran University of Medical Sciences, 2011)
Background and Aim: The hierarchical and bureaucratic form of governmental administration is changing into a new type of flexible and market-based public management called Enterpreneurial Management Revolution. According to Stevenson, entrepreneurial management comprises a number of opportunity-based management activities for the maintenance of organizations in order to have their contribution in social value creation. This research study aims to study the organizational performance of medical sciences universities of Tehran based on Stevenson Model. Materials and Methods: This research is a field study in which a structured questionnaire containing 22 main questions on the Likert Scale was distributed among the staff members of medical sciences universities in Tehran. The validity of the questionnaire was confirmed by experts and its reliability was estimated using Test- Retest Method. The Cronbach alpha coefficient was found to be 0.95. The data collection device was given to 379 staff members, of whom 325 filled it out. The data were completely recorded and then analyzed by SPSS software version 18. Results: The results of the study show that regarding entrepreneurial management approach, medical universities are at an average level. According to the present research and all related studies, this is the case in all other governmental organizations. Conclusion: The results of the study indicate that organizational restructuring, decentralization, and continuous improvement in processes are the milestones of entrepreneurial revolution strategies in medical universities and all other public organizations.